1979
DOI: 10.3109/00498257909038710
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Urinary and Biliary Metabolites of Alprenolol in the Rat

Abstract: 1. After oral administration of alprenolol to rat, 12 metabolites were isolated and characterized as trifluoroacetyl, trimethylsilyl and n-butylboronate derivatives, using a g.l.c.-mass spectrometry-computer system. Fragmentation pathways of derivatives in the mass-spectrometric analysis are discussed. 2. Metabolic reactions involved are oxidative degradation of the propanolisopropylamine side-chain, aromatic hydroxylation, oxidation of the allyl group, and conjugation. A method for direct analysis of epoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The problems involved in the preparation of TMS derivatives of carbamates have been reported by several authors (18)(19)(20), who emphasize the risk of structural transformations during GLC chromatography. For-the same reason, TMS derivatization of metabolite H 119/84 could not be used for elucidating the actual position of the hydroxy group as reported for the corresponding hydroxylated metabolites of metoprolol (21) and alprenolol (22). The accessibility of the secondary amine in the long sidechain for formation of a TMS derivative strongly o depends upon the reagent used.…”
Section: Analytical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems involved in the preparation of TMS derivatives of carbamates have been reported by several authors (18)(19)(20), who emphasize the risk of structural transformations during GLC chromatography. For-the same reason, TMS derivatization of metabolite H 119/84 could not be used for elucidating the actual position of the hydroxy group as reported for the corresponding hydroxylated metabolites of metoprolol (21) and alprenolol (22). The accessibility of the secondary amine in the long sidechain for formation of a TMS derivative strongly o depends upon the reagent used.…”
Section: Analytical Aspectsmentioning
confidence: 99%
“…The accessibility of the secondary amine in the long sidechain for formation of a TMS derivative strongly o depends upon the reagent used. We have previously reported that BSAas a silyl donator did not react with the isopropylamino group (9,21,22) but, depending upon gas-chromatographic and reagent conditions, partial N-TMS formation can occur. With a weak silyl donator, such as hexamethylenedisilazane, this reaction can be avoided,leaving the nitrogen underivatized.…”
Section: Analytical Aspectsmentioning
confidence: 99%